1999
DOI: 10.1590/s0101-81751999000600012
|View full text |Cite
|
Sign up to set email alerts
|

Abelhas Euglossini (Apidae) de áreas de Mata Atlântica: abundância, riqueza e aspectos biológicos

Abstract: ABSTRACT. Eugl ossine bees (Apidae) frem Atlantic Forest sites: abundance, richness, and bi ological aspects. Co llection data of Euglossinae males from Parque Estadual do Rio Doce (PERD) and Viçosa, both areas w ith remnants of Atlantic Rain Forest (Mata Atlântica) in Minas Gerais state, Brazil are presented. Comparisons made among three fragments with different sizes and states of di sturbance fi'om Viçosa showed difterences in abundance of most common spec ies and apparently, Eu/aema nigrita Lepeletir, 1841… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
90
1
36

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 35 publications
(29 reference statements)
12
90
1
36
Order By: Relevance
“…Seasonal differences could account for difference among habitats, although fragrance resources (Table 5) did not appear to be limited and the frequency of individuals with pollinaria attached were even slightly higher than reported elsewhere in South America (e.g., Pearson & Dressler 1985, Peruquetti et al 1999; the latter suggests a widespread fl owering of orchids and availability of fragrance during the survey period. However, studies have shown the highest diversity of species is coincident with the rainy season and declines after this period (Pearson & Dressler 1985, Hedström et al 2006b, when the seasonally abundant species disappear.…”
Section: Discussionmentioning
confidence: 76%
“…Seasonal differences could account for difference among habitats, although fragrance resources (Table 5) did not appear to be limited and the frequency of individuals with pollinaria attached were even slightly higher than reported elsewhere in South America (e.g., Pearson & Dressler 1985, Peruquetti et al 1999; the latter suggests a widespread fl owering of orchids and availability of fragrance during the survey period. However, studies have shown the highest diversity of species is coincident with the rainy season and declines after this period (Pearson & Dressler 1985, Hedström et al 2006b, when the seasonally abundant species disappear.…”
Section: Discussionmentioning
confidence: 76%
“…Euglossa cordata e Eulaema nigrita têm sido sugeridas como espécies indicadoras de ambientes secos e alterados (Peruquetti et al 1999, Silva & Rebêlo 2002, Tonhasca et al 2002, hipótese aceita neste trabalho, visto que as abundâncias dessas espécies foram muito superiores nas áreas mais perturbadas. Porém, para Euglossa cordata dois fatores devem ser considerados; 1 -A espécie também é abundante em áreas consideradas preservadas como foi visto neste estudo e também por Tonhasca et al (2002) e 2 -A difi culdade de identifi cação taxonômica de várias espécies de Euglossa, gênero ainda sem revisão taxonômica, pode estar difi cultando a identifi cação correta dentro de complexos de espécies, o que pode estar acontecendo com Euglossa cordata (Dressler 1982b).…”
Section: Resultsunclassified
“…Outra grande contribuição desses insetos é o fato de serem fortes candidatos a indicadores de qualidade ambiental de áreas naturais ou antrópicas (Peruquetti et al 1999, Tonhasca et al 2002. Estudos têm demonstrado que a fragmentação pode afetar de forma negativa a estrutura e os processos ecológicos do ecossistema, inclusive a polinização.…”
unclassified
“…A study by Murren (2002) at Panamá has shown that Eulaema cingulata (Fabricius) from a mainland site visited bait traps on an island 500 m away. Also, a number of euglossine species have been observed moving between Brazilian rainforest remnants (Raw, 1989;Tonhasca et al, 2003), although other studies carried out in Brazil have shown that males from some euglossine bee species do not cross the intervening matrix between forest fragments (Powell and Powell, 1987;Peruquetti et al, 1999).…”
mentioning
confidence: 99%